International Capital Markets : Developments and Prospects, 1982. (Occasional Papers; Occasional Paper ;, 1982)
This paper provides a review of developments and prospects in the international capital markets, including official actions affecting the markets and the role of the markets in intermediation between surplus and deficit countries, in particular the non-oil developing countries.